2003
DOI: 10.1590/s0100-204x2003000600007
|View full text |Cite
|
Sign up to set email alerts
|

Translocação e redistribuição de enxofre em plantas de milho e de soja

Abstract: Resumo -O objetivo deste trabalho foi estudar a translocação e a redistribuição de S pelo transporte acrópeto e basípeto em plantas de milho e de soja. Plantas das duas espécies foram cultivadas em solução nutritiva contendo 35 S em casa de vegetação. O 35 S aplicado em uma única raiz foi prontamente absorvido e translocado para a parte aérea, assim como para as demais raízes cultivadas na ausência de enxofre. O radioisótopo aplicado em uma única folha foi transportado tanto na direção acrópeta quanto na basíp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
7
0
7
Order By: Relevance
“…The treatment resulted in the development of nutritional disorder symptoms in B. catenulata plants, with new leaves that were light green (Supplemental Fig. 1E), demonstrating the main physiological S sink (Silva et al, 2003). This result is consistent with those reported by Malavolta (1997), who confirmed the yellowing of younger leaves as a typical symptom.…”
Section: Resultssupporting
confidence: 90%
“…The treatment resulted in the development of nutritional disorder symptoms in B. catenulata plants, with new leaves that were light green (Supplemental Fig. 1E), demonstrating the main physiological S sink (Silva et al, 2003). This result is consistent with those reported by Malavolta (1997), who confirmed the yellowing of younger leaves as a typical symptom.…”
Section: Resultssupporting
confidence: 90%
“…Given that wheat grain yield in 2005 was positively related to the Ca ( r = 0.79, p < 0.05) and S ( r = 0.70, p < 0.05) leaf contents and that corn grain yield in 2004–2005 was also positively related to Ca ( r = 0.71, p < 0.05) and S ( r = 0.89, p < 0.01) leaf contents, it is considered more probable that yield benefits imparted by gypsum resulted from increased Ca and SO 4 –S availability to the cereal crops. The explanation for this effect may be due to the lower cation exchange capacity of roots (CECR) in grasses than in legume plant species (Asher and Ozanne, 1961) and to the different behaviors in S uptake and redistribution by plants (Silva et al, 2003). Williams and Coleman (1950) found that the CECR was double in soybean as compared with corn.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, corn and wheat plants are less efficient than soybean plants in Ca uptake from the soil solution. In contrast, corn retains a greater part of the S absorbed in the root, while soybean presents greater translocation efficiency (Silva et al, 2003). Thus, corn and wheat crops require less Ca and/or SO 4 –S than the soybean crop, but they respond more to greater soil Ca and SO 4 –S availability because they are less efficient in both Ca uptake and S translocation.…”
Section: Resultsmentioning
confidence: 99%
“…As plantas de milho apresentam maior absorção radicular de S quando comparado a soja, retendo grande parte desse nutriente na própria raiz enquanto o S aplicado via folhar é transportado para todas as partes da planta. Sendo assim, a fertilização deste nutriente via foliar na cultura do milho pode ser importante em solos com baixos teores de enxofre, porém na prática existe carência de trabalhos apresentando resultados sobre o assunto (SILVA et al, 2003).…”
Section: Introductionunclassified